Flexible Scheduling For Construction Project Using Fuzzy Logic Method And Critical Path Method (CPM) - Voon, Sze Nee (Universiti Sains Malaysia, 2017)
A successful project schedule is one of the primary keys to project success. In this study, Fuzzy logic method (Decision maker’s risk index ranking value) is used to estimate the delay period of a project. It is obvious that the conventional project scheduling software is using either deterministic or probabilistic method to compute the schedule duration, delays and lags. In other words, these methods use only quantitative inputs but not qualitative aspects associated with individual activities. Project manager who lack in experience will have a significant impact on the accessed duration. The method used in this paper which determined the critical path by the lowest risk path. The risk index is computed for each individual activity. A realistic project is considered for FPERT has been prepared using Excel. This project has been periodically updated until the project completion.